Heart rate response to game-play in professional basketball players - Jiménez, A. V.; Vicente, J. G. V.; Calleja, J.; Marroyo, J. A. R.; Lopez, J. G.; Smpedro, J. (Journal of Human Sport & Exercise, 2008)
Introduction: The effectiveness of using the heart rate (HR) as an indicator of exercise intensity to monitor basketball training has been the subject of intense investigation. However, recent new regulations and a trend towards a more conditional game have prompted a need to revise field study procedures and demanded the increased specialization of game positions. Objectives. Five preseason matches played by a Profesional men`s Spanish league team LEB (Club Baloncesto León) were analyzed in terms of the HR response recorded in the four game quarters. Materials and Methods. Heart rates were recorded using Polar Team® monitors in a group of 8 players, whose playing positions were point guard (n=2), forward (n=3) or center (n=3). We recorded maxima (HRmax) and means (HRmean) for each player and also expressed rates as percentages of the individual maximum HR recorded in the 5 games (%HRmax and %HRmean). Results. For the point guards, forwards and centers, respectively, HRmax (in beats•min) were 186±11.7, 176±8.3 and 177±7.7; and HRmean (beats•min-1) were 163±14.3, 151±10.3 and 155±9.4. While similar HRmax were observed in each quarter, significant differences were detected between the %HRmax values for the point guards versus the forwards or centers. Conclusion. Our findings indicate that point guards show the highest HR and forwards the lowest. HRmax and %HRmax values were high during the first quarter and continued to increase during the game, peaking in the final quarter.